FAKTOR-FAKTOR PENGUNGKAPAN CSR DISCLOSURE (Pada Perusahaan Manufaktur yang Listing di Bursa Efek Indonesia Periode 2015-2017) - Zainal Abidin; Nur Diana; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThis research aims to determine the effect of debt, profitability, and environmental responsibility on Corporate Social Responsibility (CSR) Disclosure. The type of research used is quantitative. This research uses a purposive sampling technique. The population used in This research is 139 companies and based on criteria that have been determined for three years, resulting in 72 company samples for the period 2015-2017. analysis in This research is using multiple linear regression models with SPSS analysis tools. The results of This research indicate that the debt variable has a negative effect on Corporate Social Responsibility (CSR) Disclosure. Profitability and environmental responsibility variables have a positive and significant effect on Corporate Social Responsibility (CSR) Disclosure. Research can provide additional knowledge in the future, and can be used as a reference in making investment decisions.Keywords: Debt, Profitability, Environmental Responsibility, Corporate Social Responsibility